(3GdCYdGb GdNWjQI aj PcQ CeQGA GdTGe hGdLRjQIs - (3eMeO Hf Ydj Hf EHQGgje GdCfUGQj GdMdHj Ke GdeUQj, CHhYHO Gddg YR GdOjf, GHf TOGO,J (B684 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi Gddg GHf TOGO GdMeO ddg GdPi bU ef CfHGA GdQSd ef KHJ ahGg QShdg s
(3BNQgG (B:s
(3hJhai Gdedc GdYRjR hUGQJ Edi hdO Gdedc GdfGUQ ajeG UGQ ef GdHdGO heG RGdJ ai edcg Edi Cf CfbWYJ GdOhdg fLR GdLRA GdChd ef GdGYdGb s
(3GfXQ GdbSe GdChd ef GdJGQjN Qbe (B43s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B482 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B21 s
Keywords: (3GdJGQjNs